A study on Commonwealth export market development - The Commonwealth Secretary General (London : Commonwealth Secretariat, 1970)
This study had its genesis in the agreement of Commonwealth Heads of Government, meeting in 1965, that it was desirable to explore means by which Commonwealth trade might be encouraged and expanded.
osc 08/04/2019
Loans
Keywords: Trade; Export trade